From the journalist to writer: Pedro Beltrán and MVLL as promoters of liberalism in Peru - Llanos Illescas, Luis Fernando (2025)
Classical liberalism in Peru is a poorly addressed topic in the social sciences and in history. Therefore, the purpose of this research is to compare the figures of two liberal references, both from the 20th century and the 21st century: Pedro Beltrán and MVLL. By analyzing both figures we can see how Beltrán promoted classical liberal ideas through the newspaper La Prensa, seeking to defend economic liberalization and the construction of accessible housing to prevent the spread of barriadas. While, in the case of Vargas Llosa, he sought to defend his liberal ideals through his International Foundation for Freedom along with his opinion columns and a book called La llamada de la Tribu, focusing more on politics. Without a doubt, both characters have promoted various liberal ideas that are still in the process of consolidation in the country.